Factors affecting career choice among local and foreign university students in Malaysia - Wong, Rong Fu (2019)
Career Choice is actually an essential process where each university students will go through upon their graduation, and a correct career decision is critical as it could help to improve job satisfaction and reduce job hopping. This study is to identify the variables that could influence the career choice of university students in Malaysia. The data for this study was collected using questionnaire. A sample of 200 university students in Klang Valley was selected using convenience sampling technique and a total number of 148 responses were retrieved with valid data. By using statistical package for Social Sciences (SPSS) to analyse the data, the results revealed that Personal Interest and Self-Efficacy has significant relationship with career choice. Moreover, it was found that there is significant difference between university students’ nationality on career choice, where foreign university students have more favorable perceptions towards the career choice.